VLSI Architectures for Future Video Coding - Martina, Maurizio, 1975- (Institution of Engineering & Technology, 2019)
This book examines future video coding from the perspective of hardware implementation and architecture design. The book identifies challenges in deploying VLSI architectures for video coding and postulates potential solutions with reference to recent research.
Keywords: Digital video.; Coding theory.; Integrated circuits -- Very large scale integration.; Video compression.; elektronické knihy; electronic books